2022
DOI: 10.1021/acsnano.2c08906
|View full text |Cite
|
Sign up to set email alerts
|

A Programmable Plasmonic Gas Microsystem for Detecting Arbitrarily Combinated Volatile Organic Compounds (VOCs) with Ultrahigh Resolution

Abstract: For gas sensors, the ultrasensitive and highly selective detection of multiple components is of great significance in a wide range of applications extending from environment to healthcare, which is still a long-term challenge due to the single sensing mechanism of most sensors. Here, we combine the advantages of microfluidic chips and surface-enhanced Raman spectroscopy (SERS) spectra to fabricate a smart single-chip for simultaneously detecting an arbitrary combination of VOCs that incorporates different dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Furthermore, Yang and researchers demonstrated that MXene placed on a 3D transferable microfluidic SERS substrate could robustly sense gases, namely, 2,4‐dinitrotoluene (DNT), indole, and odoriferous benzaldehyde with a LOD in the range 10–50 ppb. [ 109 ] Not just chemical species, even bacteria like E. coli and B. subtilis were sensitively detected using self‐assembled MXene Au nanocomposite as a label‐free rapid substrate. [ 110 ] Besides, wrinkled surface features were produced by the conformal blanketing of a few layers of MXene on an Au assembly (MXene blanketed Au nanoparticle) as a SERS substrate assisted in enhancing the EM effect, and the combination inflated the CT and EM effects.…”
Section: Mxene‐based Materials For Sersmentioning
confidence: 99%
“…Furthermore, Yang and researchers demonstrated that MXene placed on a 3D transferable microfluidic SERS substrate could robustly sense gases, namely, 2,4‐dinitrotoluene (DNT), indole, and odoriferous benzaldehyde with a LOD in the range 10–50 ppb. [ 109 ] Not just chemical species, even bacteria like E. coli and B. subtilis were sensitively detected using self‐assembled MXene Au nanocomposite as a label‐free rapid substrate. [ 110 ] Besides, wrinkled surface features were produced by the conformal blanketing of a few layers of MXene on an Au assembly (MXene blanketed Au nanoparticle) as a SERS substrate assisted in enhancing the EM effect, and the combination inflated the CT and EM effects.…”
Section: Mxene‐based Materials For Sersmentioning
confidence: 99%
“…Therefore, detection of toxic gases in the living environment is very necessary for prevention of diseases and maintenance of human health [ 73 ]. Plasmonic sensors are also widely used in gas sensing, such as detecting hydrogen [ 74 , 75 , 76 , 77 ], nitrogen dioxide [ 78 ] and organic volatile gases [ 79 , 80 ].…”
Section: Applications Of Plasmonic Biosensorsmentioning
confidence: 99%
“…A gas biosensor with small volume, fast reading speed and low cost can simultaneously identify nine different gases with high sensitivity, high selectivity and high robustness. Moreover, the authors also claim that their sensors can maintain high selectivity without being disturbed by complex detection environments in indoor pollution detection and exhaled gas detection [ 79 ].…”
Section: Applications Of Plasmonic Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaseous molecules have a lower number density and higher kinetic energy than solid or liquid samples, which hinders their capture on SERS hotspots. Due to the possibility of a smaller Raman scattering cross section, they may also necessitate more sensitive SERS probes. Currently, there are two primary solutions for achieving SERS application in the detection of gaseous molecules: (i) develop a simple and low-cost method to construct substrates with highly ordered plasmon nanostructure (i.e., hotspots) to ensure the high sensitivity and reproducibility of SERS signal of Raman weak strength molecules; , (ii) explore an efficient method to bring gaseous molecules to the surface of plasmon nanostructures and ensure uniform absorption of the gaseous molecules . Nevertheless, due to trace concentrations, high mobility, and complex matrix interference in real samples, the majority of SERS-active substrates face obstacles, such as poor affinity between the plasmon surface and analytes, undifferentiated target concentration/enrichment, interfering molecules, etc.…”
mentioning
confidence: 99%